2021
DOI: 10.3390/molecules26144137
|View full text |Cite
|
Sign up to set email alerts
|

Clitorienolactones and Isoflavonoids of Clitorea ternatea Roots Alleviate Stress-Like Symptoms in a Reserpine-Induced Zebrafish Model

Abstract: Clitorea ternatea has been used in Ayurvedic medicine as a brain stimulant to treat mental illnesses and mental functional disorders. In this study, the metabolite profiles of crude C. ternatea root extract (CTRE), ethyl acetate (EA), and 50% aqueous methanol (50% MeOH) fractions were investigated using ultrahigh-performance liquid chromatography–diode array detector–tandem mass spectrometry (UHPLC–DAD–MS/MS), while their effect on the stress-like behavior of zebrafish, pharmacologically induced with reserpine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 59 publications
(77 reference statements)
1
6
0
Order By: Relevance
“…In order to improve screening efficiency and conduct high-throughput screening, we established reserpine-induced models on zebrafish. It has been reported in the literature that 20 and 40 mg/L reserpine did not cause significant acute behavioral effects, and locomotor ability was significantly reduced after 7 days, similar to the locomotor retardation observed in depression [30][31][32][33]. Based on this research, we found that when the concentration of reserpine was 10 mg/L, it could cause zebrafish to show reduced locomotor ability and exploratory behavior.…”
Section: Discussionsupporting
confidence: 83%
“…In order to improve screening efficiency and conduct high-throughput screening, we established reserpine-induced models on zebrafish. It has been reported in the literature that 20 and 40 mg/L reserpine did not cause significant acute behavioral effects, and locomotor ability was significantly reduced after 7 days, similar to the locomotor retardation observed in depression [30][31][32][33]. Based on this research, we found that when the concentration of reserpine was 10 mg/L, it could cause zebrafish to show reduced locomotor ability and exploratory behavior.…”
Section: Discussionsupporting
confidence: 83%
“…Butterfly pea flowers are used in traditional medicine to stimulate the brain in mental illness and mental functional disorders. Due to clitorienolactone and isoflavonoid constituents in butterfly pea flower therefore it is beneficial in lowering stress and depression (Ngadni et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, knottin peptides, although considerably stable to enzymatic attack, when hydrolyzed in the gut may act as a good source of dietary amino acids while the unhydrolysed stable peptide has the potential to trigger changes in the gut microbiota [ 32 ] owing to their broad bioactivity, antimicrobial activity in particular [ 33 ]. Medicinal plants and phytomedicines rich in knottin-like peptides commonly taken as food appear to be good sources of essential amino acids and low molecular weight peptides [ 34 ] needed for the proper physiological functioning and prevention of several metabolic diseases [ 35 ]. These essential and other types of important dietary amino acids have thus been classified as functional amino acids [ 35 ].…”
Section: Applications Of Knottin-rich Peptidesmentioning
confidence: 99%